Financial Performance Analysis through Trend Analysis in the Profit and Loss Report of PT Bukalapak.com Tbk - Nurafni Oktaviyah,; Samirah Dunakhir,; Hariany Idris, (International Economic Conference of Business and Accounting, 2024)
This study aims to analyze the financial performance of PT Bukalapak.com Tbk in 2020-2023 based on the company's income statement using the trend analysis method. Trend analysis will be carried out using the vertical trend analysis method (common size) and horizontal trend analysis (time series). The basic comparison is net income for vertical trend analysis and the base year used as a comparison is 2020 for horizontal trend analysis. The data in this study are explained descriptively using a quantitative research approach. The results of the study show that the financial performance of PT Bukalapak.com Tbk in 2020-2023 continues to increase which increases the increase in net income every year. The achievement of this performance side is not followed by improvements in operating expenses, especially the cost of revenue. The trend analysis carried out by analyzing both vertical and horizontal trends shows that the cost of revenue continues to experience a significant increase. Sales and marketing expenses that continue to decline and profit income that continues to increase also affect the company's performance. While other items on the income statement experience different changes each year.